Measuring Clinical Efficacy Through the Lens of Audit Data in Different Adult Eating Disorder Treatment Programmes - Li, Zhuo; Dandil, Yasemin; Toloza, Cindy; Carr, Anna; Oyeleye, Oyenike; Kinnaird, Emma; Tchanturia, Kate (Frontiers in Psychiatry, 2020)
Background: Audit data is important in creating a clear picture of clinical reality in clinical services, and evaluating a variety of outcomes. This paper explored the data from an audit of a large national eating disorder (ED) service and evaluated the outcome of inpatient and day treatment programmes for anorexia nervosa (AN) patients with and without autistic traits. Methods: 476 patients receiving treatment for AN at inpatient (IP), day-care (DC) and step-up (SU) programmes were assessed at admission and at discharge on the following measures: autistic traits, body-mass-index (BMI), ED symptoms, depression and anxiety symptoms, work and social functioning, and motivation for change. Outcomes were analysed first at a within-group level based on change in mean scores and then at an individual level based on the clinical significance of improvement in eating disorder symptoms. Results: 45.5% of DC and 35.1% of IP patients showed clinically significant changes in ED symptoms following treatment with no significant difference between the two groups. Co-occurring high autistic traits positively predicted improvement in ED symptoms in IP setting, but was a negative predictor in DC. In IP, more inpatients with high autistic traits no longer met the BMI cut-off for AN compared to low trait peers. In terms of general psychopathology, patients with AN and high autistic traits exhibited more severe depression symptoms, anxiety symptoms and social functioning impairment than their peers without high traits on admission, and these symptoms stayed clinically severe before their discharge. Conclusions: DC can be as effective in improving ED symptomatology as IP. However, for AN patients with high autistic traits, IP with individualised and structured routine care may be a preferred model of treatment.